2010
DOI: 10.2147/opth.s13278
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer evaluation in multiple sclerosis with spectral domain optical coherence tomography

Abstract: Purpose: Histopathologic studies have reported retinal nerve fiber layer (RNFL) thinning in various neurodegenerative diseases. Attempts to quantify this loss in vivo have relied on time-domain optical coherence tomography (TDOCT), which has low resolution and requires substantial interpolation of data for volume measurements. We hypothesized that the significantly higher resolution of spectral-domain optical coherence tomography (SDOCT) would better detect RNFL changes in patients with multiple sclerosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
(47 reference statements)
2
15
0
2
Order By: Relevance
“…Parisi et al [7], using an early generation of TDOCT technology, demonstrated reduced temporal and overall RNFL thickness in MS eyes with and without ON when compared to the controls. Other investigators demonstrated that using SDOCT technology showed mean RNFL thinning in MS patients, and that eyes with a history of ON had thinner RNFL measurements than those without a history of ON [6,8,18]. In this study, our data demonstrated the thinning of RNFL in Chinese patients with MS.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Parisi et al [7], using an early generation of TDOCT technology, demonstrated reduced temporal and overall RNFL thickness in MS eyes with and without ON when compared to the controls. Other investigators demonstrated that using SDOCT technology showed mean RNFL thinning in MS patients, and that eyes with a history of ON had thinner RNFL measurements than those without a history of ON [6,8,18]. In this study, our data demonstrated the thinning of RNFL in Chinese patients with MS.…”
Section: Discussionsupporting
confidence: 69%
“…Our data showed that the average RNFL in patients with a VF defect was thinner than that in patients without a VF defect. Khanifar et al [6] found that the peripapillary RNFL was thinning significantly over 5 years of disease, even in MS patients without a history of ON. Our results showed that the average RNFL thickness was thinner when the disease duration was >24 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…соавт. [6], которые, применив спектральный ОКТ Heidelberg Spectralis, продемонстрировали значительное истончение СНВС на фоне РС в сравнении с его нормальной толщиной в здоровых глазах. У этих больных наиболее выраженное истончение отмечено в глазах с ОН.…”
Section: рис 4 ежегодная разница показателей окт для пациентов полunclassified
“…Spectral domain-OCT has shown promising results based on RNFL and GC-IPL analyses, identifying the presence of RGC and optic nerve damage in AD. More recently, SD-OCT technology has been used in studies of other CNS and neurodegenerative disorders such as Parkinson's disease [58][59][60] and multiple sclerosis 61 , to evaluate retinal parameters including RNFL thickness, inner retinal layer thickness and macular thickness. There is definitely potential for this technology to be used in further studies of neurodegenerative diseases.…”
Section: Future Directionsmentioning
confidence: 99%